Assessment of the impact of non-state actors in the support for obstetric fistula care: Matters arising - Abduls-Salam, RA; Lawal, OO; Morhason-Bello, IO; Bello, OO; Babawarun, TO; Ojengbede, AO (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To review the impact of support of non-state actors on communal OF repair effort in fistula repair Centre. Methods: We reviewed the support given for OF repairs at Adeoyo Maternity Hospital, Ibadan from 2013 to 2018. The type of support was either Partial or Full support; involved support from various organizations such as Extended Hands, GWIN, Faith Hookes Foundation, Engenderhealth/USAID. Partial support was provided by above-listed organizations between 2013- 2016. However, sustained Full support was provided by Fistula carePlus/Engenderhealth/USAID between 2017 and 2018. Results: Partial support involved supply of equipment, health education, radio jingles, fistula repairs; while Full support included supply of medical consumable, mobilization of fistula clients/client mobilization using social workers, feeding of clients for minimum of 2 weeks, provision of power backup, mobilization and remuneration of OF surgeons and manpower, in addition to those listed above. One hundred, eighty-seven women benefitted from support. Fistula types ranging from obstetric, iatrogenic and traumatic fistula were repaired using both pooled effort and routine repair models. During partial support, 70(37.4%) women were repaired compared to 117 (62.6%) when sustained full support was provided. All women freely accepted participation in the supported repair program. Conclusions: There is a compelling improvement in patronage, access to care and opportunity to develop the skills of enthusiast among the health-workers; and thus a need for more commitment in our quest to eliminate obstetric fistula.